Ответ:
Объяснение:
№7
1-sinx*ctgx*cosx
ctgx=cosx/sinx
1 - sinx*cosx*cosx/sinx=1-![(cosx)^{2} (cosx)^{2}](https://tex.z-dn.net/?f=%28cosx%29%5E%7B2%7D)
По основному тригонометрическому тождеству
+
=1
=1 - ![(cosx)^{2} (cosx)^{2}](https://tex.z-dn.net/?f=%28cosx%29%5E%7B2%7D)
Поэтому имеем: ![(sinx)^{2} (sinx)^{2}](https://tex.z-dn.net/?f=%28sinx%29%5E%7B2%7D)
Ответ:![(sinx)^{2} (sinx)^{2}](https://tex.z-dn.net/?f=%28sinx%29%5E%7B2%7D)
№8
y=(1/3)*x^3-x^2
z=(1/3)*3*x^2 - 2x= x^2 - 2x (производная)
z(1)= 1^2-2*1=1-2= - 1
Ответ: -1